2022
DOI: 10.1177/10547738221112756
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Assessment of the Breastfeeding Self-Efficacy Scale-Short Form: A Confirmatory Factor Analysis of Indonesian Mothers

Abstract: This study aimed to evaluate the psychometric properties of the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF) in Indonesian postpartum women. We conducted a cross-sectional study including 237 postpartum women in Yogyakarta City, Indonesia. Participants completed the BSES-SF, Edinburgh Postnatal Depression Scale (EPDS), and Hospital Anxiety and Depression Scale (HADS). Construct validity, internal reliability, and divergent validity were examined using confirmatory factor analysis, Cronbach’s alpha, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The most common time to assess breastfeeding self-efficacy was in-hospital during the postpartum period ( n = 17; 41%). However, the timing of assessment varied among some studies with assessment of breastfeeding self-efficacy conducted during the third trimester of pregnancy [ 26 , 27 ], postnatally (time not reported) [ 28 , 29 ], at 1 week [ 27 ], or open time periods such as two to six weeks [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common time to assess breastfeeding self-efficacy was in-hospital during the postpartum period ( n = 17; 41%). However, the timing of assessment varied among some studies with assessment of breastfeeding self-efficacy conducted during the third trimester of pregnancy [ 26 , 27 ], postnatally (time not reported) [ 28 , 29 ], at 1 week [ 27 ], or open time periods such as two to six weeks [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, women with higher scores on the EPDS had significantly lower BSES scores. Using other measurements of depression, Boateng et al [ 37 ] reported a negative correlation between Centre for Epidemiological Studies Depression Scale (CES-D) [ 60 ] and BSES-SF scores and two researchers [ 29 , 54 ] reported a negative correlation between the HADS depression subscale and BSES-SF scores. All three studies that examined the correlation between anxiety and BSES-SF, researchers found a negative correlation between anxiety and BSES-SF scores, using different measurement tools [ 21 , 29 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation